Neogene and Quaternary geodynamic evolution of the Italian peninsula: the contribution of paleomagnetic data - Leonardo Sagnotti; Fabio Florindo; Laura Alfonsi; Antonio Meloni; Fabio Speranza; Aldo Winkler (Annals of Geophysics, 1997)
Paleomagnetism has played an important role in the development of geodynamic models for the Italian peninsula. Paleomagnetic data from this area have been increasingly reported since the late 1960s, placing important constraints on geodynamics. A brief outline of the main concepts underlying a paleomagnetic study is provided in the first part of this paper. We also discuss the criteiia for the assessment of the reliability of paleomagnetic data. Finally,the data collected over the past 25 years in peninsular and insular Italy are synthetically reviewed, discussing the main implications for the geodynamic evolution of the Tyrrhenian - Apennines foreland system.